Pengaruh Gaya Kepemimpinan, Budaya Organisasi Terhadap Kinerja Karyawan Pada Toeng Market Malang - Isvandiari, Any (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2018)
The goals of this research is attempt to know how the effect of leadership style to the employees job performance and leadership style together with organization’s culture to the employees job performance at Toeng Market Malang. This research is a causal research, population of this research is 69 employees. Sample of this research is 69 employees by used full sampling technique. Hypothesis is tested by used t test (as partially) and F test (as simultaneously).The t test result shows that leadership style has positively and significant effect to the employees job performance, organization’s culture has no effect positively and significant., but leadrship style and organization’s culture simultanueously have positively and significant effect on the job performance.